Perancangan UI/UX Sistem Informasi Akademik Menggunakan Pendekatan Design Thinking - Shiddieq, Diqy Fakhrun; Nurhayati, Dwi (Jurnal Ilmiah SINUS, 2025)
The significant shift in the utilization of technology has led most universities worldwide to adopt various digital platforms. Academic information systems represent one such technological implementation that plays a crucial role in the retention and success of academic and non-academic activities within higher education institutions. Although many institutions, including Garut University, have developed academic information systems, UI/UX remain significant issues. Suboptimal interface design can cause user frustration, reduce productivity, decrease cognitive performance, affect users' emotional responses, and even lower the technology adoption rate. This research was conducted to provide system recommendations by analyzing and designing the UI/UX of the academic information system at Garut University using the design thinking method. The recommendations are presented as prototypes developed using the Figma. The prototypes were tested with 30 respondents using the HEART Framework, presented in a goal-signal-metric format, with the highest or strongly agreed responses recorded for all variables: happiness at 58.89%, engagement at 57.78%, adoption at 76.67%, retention at 66.67%, and task success at 61.11%. These results indicate that the adoption variable obtained the highest score, suggesting that the information within the academic information system meets user needs, is easy to learn, and that the system quality is rated as good.